Architecture without Land : access to land, secured with land tenure as development strategy in critical neighbourhoods, in South Africa - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2018)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2018.